Comparison of diagnostic spectrum between inflammation of unknown origin and fever of unknown origin: A systematic review and meta-analysis - Betrains, Albrecht; Moreel, Lien; Mulders-Manders, Catharina M.; Auwaerter, Paul G.; Torné-Cachot, Joaquim; Weitzer, Friedrich; Terasawa, Teruhiko; Ly, Kim H.; Schönau, Verena; Blockmans, Daniel; Wright, William F.; Rovers, Chantal; et al. (European Journal of Internal Medicine, 2024)
Background: Patients with inflammation of unknown origin (IUO) and fever of unknown origin (FUO) are commonly considered a single population. Differences in underlying causes between both groups may steer the diagnostic work-up. Methods: PubMed, Embase, Web of Science, and ClinicalTrials.gov were searched from July 2009 through December 2023. Studies including both FUO and IUO patients with a sample size of ≥20 were considered. The primary outcome was the difference in the rate of patients affected by predefined diagnostic categories according to meeting FUO or IUO criteria. Data were pooled using random-effects models. Results: A total of 8 studies met criteria for inclusion, with a total of 1452 patients (466 with IUO and 986 with FUO). The median rate of IUO patients among the included studies was 32 % (range 25–39 %). Patients with IUO had a lower likelihood of infection (OR 0.59 [95 % CI; 0.36–0.95]; I2 0 %). There were no significant differences in the rate of noninfectious inflammatory disorders, malignancies, miscellaneous disorders, or remaining undiagnosed. Comparison of diagnostic subgroups revealed that IUO patients were less likely to have systemic autoinflammatory disorders (OR 0.17 [95 % CI, 0.05–0.58]; I2 42 %) and more likely to have vasculitis (OR 2.04 [95 % CI, 1.23–3.38]; I2 21 %) and rheumatoid arthritis or spondylarthritis (OR 3.52 [95 % CI, 1.16–10.69]; I2 0 %). Conclusion: Based on our findings, there is little reason to assume that FUO and IUO patients would benefit from a different initial diagnostic approach.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Diagnostic categories; Diagnostic spectrum; FUO; IUO